2014
DOI: 10.1159/000368463
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Intrarenal Renin-Agiotensin System Contributes to Renal Damage in High-Salt Induced Hypertension Rats

Abstract: Background/Aims: To investigate the change of intrarenal renin-agiotensin system (RAS) and its role in high-salt induced hypertension. Methods: Wistar rats were divided into normal-salt (NS), high-salt diet (HS) and high-salt diet with Losartan group (HS+L), for 6 weeks. Systolic blood pressure (SBP) was monitored. Blood and urine samples were collected every 2 weeks. Angiotensinogen (AGT) was measured by ELISA. AGT mRNA and protein were measured by real-time PCR and immunohistochemistry. Renin activity and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…This observation was also confirmed by Chandramohan et al, who suggested that high-salt diet lowers plasma renin activity but increases the number of kidney angiotensin II (Ang II)-positive cells and Ang II type 1 receptor (AT1R) in DS rats [26]. In a recent study, Wu et al [27] reported that hypertension induced by high salt levels and renal damage causes the upregulation of renal cortex renin, AGT, and Ang II; in addition, the blockage of AT1R decreased the proteinuria in Wistar rats. These observations are consistent with the results of our study, in which high salt intake increased the mRNA expression of RAS components in the renal cortex, and the blockage of the angiotensin converting enzyme (ACE) and AT1R decreased the proteinuria.…”
Section: Discussionmentioning
confidence: 58%
“…This observation was also confirmed by Chandramohan et al, who suggested that high-salt diet lowers plasma renin activity but increases the number of kidney angiotensin II (Ang II)-positive cells and Ang II type 1 receptor (AT1R) in DS rats [26]. In a recent study, Wu et al [27] reported that hypertension induced by high salt levels and renal damage causes the upregulation of renal cortex renin, AGT, and Ang II; in addition, the blockage of AT1R decreased the proteinuria in Wistar rats. These observations are consistent with the results of our study, in which high salt intake increased the mRNA expression of RAS components in the renal cortex, and the blockage of the angiotensin converting enzyme (ACE) and AT1R decreased the proteinuria.…”
Section: Discussionmentioning
confidence: 58%
“…Many studies have focused on the relationship between local RAS activation and high sodium intake [37, 38], and some authors have concluded that high dietary salt induces the inappropriate activation of the local RAS [39]. In patients with hypertension, abnormal activation of circulatory RAS is responsible for the maintenance of high BP [40], while tissue RAS activation is closely related to the target organ damage and malfunction [41]. The overexpression of ACE and AT1R in the DS rats of the HS group was probably associated with the unfavorable responsiveness of the small arteries to vasoactive agents, which led to arteriolar remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Since the characteristics of these inbred rats tend to be very consistent, we still obtained meaningful results. In previous studies with DS rats, a similar sample size was used [23, 41]. Second, the conclusions drawn from an animal study cannot be simply extrapolated to humans.…”
Section: Discussionmentioning
confidence: 99%
“…There are important data both about the relationship of the salinity of the diet and the effect of losartan with the intrarenal RAS Szauder/Csajági/Major/Pavlik/Ujhelyi: Effect of the Twice-Daily Administration of Perindopril and Losartan and the plasma thromboxane A2 level and also about the renoprotective effect of losartan. The effect of losartan in the change of intrarenal RAS: with Wistar rats in high-salt diet, Losartan failed to reduce SBP but abolished the increase of proteinuria, renal cortex renin, angiotensinogen, angiotensin II and urinary angiotensinogen when compared with high salt group [31]. There are similar accounts of the renal protective effect: the losartan/thiazide combination therapy attenuated glomerular overload, indicating that this therapy may provide glomerular protection in patients with an elevated GFR without causing prolonged damage to renal function [32].…”
Section: Introductionmentioning
confidence: 99%